2005
DOI: 10.1007/s11064-005-6978-1
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic Properties of Cannabidiol at 5-HT1a Receptors

Abstract: Cannabidiol (CBD) is a major, biologically active, but psycho-inactive component of cannabis. In this cell culture-based report, CBD is shown to displace the agonist, [3H]8-OH-DPAT from the cloned human 5-HT1a receptor in a concentration-dependent manner. In contrast, the major psychoactive component of cannabis, tetrahydrocannabinol (THC) does not displace agonist from the receptor in the same micromolar concentration range. In signal transduction studies, CBD acts as an agonist at the human 5-HT1a receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
488
1
31

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 750 publications
(529 citation statements)
references
References 39 publications
9
488
1
31
Order By: Relevance
“…In addition to 5-HT 1A agonism, the same study presented evidence for CBD binding to the 5-HT 2A receptor. In NIH/3T3 cells, CBD (8-32 μM) served as a partial agonist of the 5-HT 2A receptor with weaker efficacy than its action at the 5-HT 1A receptor [26]. 5-HT receptors are also implicated in autonomic control [47], and again here CBD has been shown to modulate 5-HT 1A -mediated responses in vivo [42].…”
Section: Serotonin Receptorsmentioning
confidence: 61%
See 2 more Smart Citations
“…In addition to 5-HT 1A agonism, the same study presented evidence for CBD binding to the 5-HT 2A receptor. In NIH/3T3 cells, CBD (8-32 μM) served as a partial agonist of the 5-HT 2A receptor with weaker efficacy than its action at the 5-HT 1A receptor [26]. 5-HT receptors are also implicated in autonomic control [47], and again here CBD has been shown to modulate 5-HT 1A -mediated responses in vivo [42].…”
Section: Serotonin Receptorsmentioning
confidence: 61%
“…CBD may also act via serotonin (5-HT) receptors [26,[42][43][44][45]. The 5-HT 1A receptor is coupled to G protein G i/o, where it is thought to mediate inhibitory neurotransmission [46].…”
Section: Serotonin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms underlying the anxiolytic effects of 5-HT 1A R activation are complex, varying between both brain region, and pre-versus postsynaptic locus, and are not fully established [56]. While in vitro studies suggest CBD acts as a direct 5-HT 1A R agonist [57], in vivo studies are more consistent with CBD acting as an allosteric modulator, or facilitator of 5-HT 1A signaling [58].…”
Section: -Ht 1a Receptorsmentioning
confidence: 99%
“…CBD has minimal affinity for CB1 receptors (Pertwee, 1997b), although it appears to interact with the endocannabinoid system via fatty acid amide hydrolase (Watanabe et al, 1996) or through the putative anandamide membrane transporter (Bisogno et al, 2001). CBD also has been found to have agonist activity at TRPV1 (Bisogno et al, 2001) and at 5-HT1A receptors (Russo et al, 2005). In addition, prior research has suggested that metabolic factors may account for interactions between CBD and THC, as inhibition of the metabolism of THC via interactions with P450 enzymes has been observed following large doses of CBD (Bornheim et al, 1993a;Bornheim et al, 1995a).…”
Section: Putative Mechanisms For Thc and Cbd Interactionsmentioning
confidence: 99%